PENGARUH PENGUASAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI, PENGALAMAN PENDIDIKAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA GURU PENDIDIKAN ANAK USIA DINI (PAUD) NONFORMAL SE-KECAMATAN SEMANU KABUPATEN GUNUNGKIDUL TAHUN AJARAN 2013/2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The Influence Mastery of Information and Communication Technology, Educational Experience, and  working Motivation to the teachers Working Productivity of  Early Childhood Education (ECE) nonformal in Semanu Gunungkidul Academic Year 2013/2014.The purposes of this research  to analyze the influence mastery of information and communication technology, educational experience, and working motivation to the teachers working productivity of ECE non-formal in Semanu either simultaneously and partially.The experiment was conducted of ECE nonformal institutions in Semanu the academic year 2013/2014 with a population of 150 teachers. The sample was 113 teachers. Technique of determining the number of samples refers to the nomogram table Harry King with base error rate of 5% and the distribution of the sample proporsional. Data collected through a questionnaire. Validation of instruments used, namely the construction of the validation test instrument reliability Cronbach alpha technique is tested on 30 samples taken at random. Prerequisite  analysis test were normality test, and test linearity multikolinieritas. The data analysis used were multiple regression test, F test and partial correlation test and coefficient of determinasi.The results of the this research showed: 1) There was a positiive that significant influence mastery of information technology and communications, educational experiences, working motivation simultaneously to the teachers working  productivity of non-formal ECE in Semanu. The Results of partial correlation analysis showed (2) There was no a positive that significant influence mastery of information and communication technologies to the teachers working productivity of non-formal ECE in Semanu. (3) There was a positive that significant influence of the educational experience to the teachers working  productivity of non-formal ECE in Semanu. (4) There was a positive that significant influence of the working motivation to the teachers working  productivity of non-formal ECE in Semanu.